Epidemiologia dos eventos adversos não infecciosos e infecciosos relacionados à assistência em unidade de terapia intensiva de adulto - Elisa Caroline Pereira Assad (2011)
OBJECTIVES: To determine the nature and incidence of adverse noninfectious and infectious events and identify contributing factors for these events in adult intensive care unit (ICU). METHODOLOGY: A historical cohort study was conducted using data collected from January 2009 through December 2009 of consecutive patients admitted in four private medical-surgical ICU. The dependent variable was the occurrence of adverse noninfectious and infectious events. Adverse noninfectious events were recorded using predefined criteria. The National Healthcare Safety Network criteria for infectious events were adopted. The independent variables were age and gender of the patient, length of ICU stay, use of mechanical ventilation (MV) and central vascular catheter (CVC) and ICU structural and process variables. In the descriptive analysis t Student test for continuous variables and the Pearson qui-square for categorical variables were applied. The Bonferroni method was used for multiple comparisons. Logistic regression models were fit to assess the net effect of each independent variable on the odds of occurrence of infectious and noninfectious adverse events. RESULTS: 2110 patients met eligibility criteria. Of these, 56,5% were female, mean age ± SD was 62,1 ± 21,2 years-old and mean length of stay ± SD was 7,12 ± 12,93 days. The incidence density rate of all events was 139,2 events/1000 patient-days in 31,2% of eligible patients, with 25,2 infectious events/1000 patient-days in 11,2% of patients, and 114,0 adverse noninfectious events/1000 patient-days in 29,1% of patients. More than 75% adverse noninfectious events were CVC, MV and other invasive devices associated. The ventilator-associated pneumonia was the most common infectious events (28,04% of these events). After controlling for other significant factors, the overall patient adverse noninfectious and infectious events rate was strongly associates with length of ICU stay (OR= 1,17; 95% CI= 1,14-1,19), and with central-line (OR= 2,77; 95% CI= 2,20-3,47) and ventilator (OR= 1,36; 95% CI= 1,08-1,72) use. The odds for overall occurrence of adverse noninfectious and infectious events was significantly higher in all ICUs in relation to ICU2. When comparing units, organizational process measured by the score obtained for its certified management system was the only relevant difference between the units. The ICU had 22 points, and the others, 1 (ICU3 and ICU4) and 4 points (ICU1). CONCLUSIONS: Critically ill adults are exposed to a numerous adverse noninfectious and infectious events related to the healthcare. Several risk factors independently contributed to these events occurrence. Focusing on these contributing factors is important for reducing and preventing these hazardous events in this high risk population. Process improvement using available certifiable models decreases the risk of infectious and noninfectious complications.